JUSTIFY WHETHER CELL AND GENE THERAPY WAS HALAL - Ika Krisnawati, Dyah; Khafid, Muhamad; Martining Wardani, Erika; Rahayu, Dwi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
One of the responsibilities of Muslims is to eat halal food. Halal has become a universal signal for ensuring the quality of products and living standards due to obedience and commitment. For Muslims, the availability of halal items is a crucial necessity. As a result, the government is now required to provide halal goods, particularly in nations where the majority population is Muslim. Product awareness affects consumer behavior when selecting items in addition to halal certification. For Muslims, it is essential to have the necessary knowledge while purchasing and consuming halal items. It is crucial since a number of non-Muslim sources in addition to Muslims provide halal-certified goods. The use of pharmaceutical ingredients generated from animals is a significant source of concern for certain customers who have religious or cultural restraints. The use of gene therapy must be adjusted to the type of disease to be treated. Diseases and their genetic relationships must be known first before gene therapy is carried out. If a gene related to a particular disease can be identified, the potential for the disease to be treated will be even greater. Similar with above statement mention that when developing halal pharmaceuticals, it is necessary to investigate alternative materials that meet halal standards while reducing the usage of essential chemicals, as well as several key principles that must be obeyed. As a therapeutic ingredient, everything is regulated by the US Food and Drug Administration regulations. (FDA.gov) The FDA regulates everything regarding cell and gene therapy, starting from safety testing of human cells, the use of animal material for cell and gene therapy purposes, donor eligibility regulations to testing donors of human cells. Regarding whether cell and gene therapy can be categorized as halal or not, it can be seen from whether all the procedures and equipment used have met the requirements in the halal certification process or not.